2001
DOI: 10.4049/jimmunol.166.3.1823
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia Outer Protein P of Yersinia enterocolitica Simultaneously Blocks the Nuclear Factor-κB Pathway and Exploits Lipopolysaccharide Signaling to Trigger Apoptosis in Macrophages

Abstract: Exposure of macrophages to bacteria or LPS mediates activation of signaling pathways that induce expression of self defense-related genes. Pathogenic Yersinia species impair activation of transcription factor NF-κB and trigger apoptosis in macrophages. In this study, we dissected the mechanism of apoptosis induction by Yersinia. Selectively, Yersinia enterocolitica strains producing the effector protein Yersinia outer protein P (YopP) hampered NF-κB activation and subsequently conferred apoptosis to J774A.1 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
183
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(199 citation statements)
references
References 36 publications
14
183
0
2
Order By: Relevance
“…Orth et al (1999) made the key observation that YopJ can bind to multiple members of the MAPK kinase superfamily, including MKKs and IKKb, and suppress their activation. The interaction between YopJ and IKKb was also confirmed by co-immunoprecipitation from macrophages (Denecker et al, 2001;Ruckdeschel et al, 2001).…”
Section: Yopjmentioning
confidence: 65%
“…Orth et al (1999) made the key observation that YopJ can bind to multiple members of the MAPK kinase superfamily, including MKKs and IKKb, and suppress their activation. The interaction between YopJ and IKKb was also confirmed by co-immunoprecipitation from macrophages (Denecker et al, 2001;Ruckdeschel et al, 2001).…”
Section: Yopjmentioning
confidence: 65%
“…Twenty-four hours after transfection, HEK293 cells were serum-starved for 18 -20 h, then stimulated as indicated. J774A.1 cells were transfected with 0.33 g of pSV-␤-galactosidase expression vector and 0.66 g of the plasmid of interest (16). Three hours after transfection, J774A.1 cells were treated with MG-132 and stimulated 30 min later.…”
Section: Analysis Of Morphology Of Transfected Cellsmentioning
confidence: 99%
“…To identify the transfected cells, the cells were fixed and stained with 5-bromo-4-chloro-3-indolyl ␤-D-galactoside (X-gal) at the time points indicated. For assessment of cell death, the morphology of blue transfected cells was determined using light microscopy (7)(8)(9)(10)16). Every single transfected cell was analyzed for an apoptotic appearance.…”
Section: Analysis Of Morphology Of Transfected Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, LPS was reported to cause cell death of conA or IFN-γ primed macrophages and to enhance cell death induced by the Yersinia baccillus [17,20,21]. Intriguingly, it was found that zVAD and boc-D, pan-caspase inhibitors that inhibit apoptosis in many different cells, not only had no inhibitory effect on LPS-induced apoptosis in INF-γ primed macrophages but also by themselves induced susceptibility to LPS-induced cell death in macrophages [22].…”
Section: Introductionmentioning
confidence: 99%